First Pleistocene South American Teratornithidae (Aves): new insights into the late evolutionary history of teratorns. Issue 2 (4th March 2021) - Cenizo, Marcos; Noriega, Jorge I.; Vezzosi, RaúL I.; Tassara, Daniel; Tomassini, Rodrigo
ABSTRACT: The first unequivocal records of teratornithid birds from the Pleistocene of South America are here described, adding a new member, and the largest, to this highly diversified guild of large carnivorous flying birds that lived during these times in the Americas. The new specimens come from four fossiliferous localities of Central Argentina that range in age from the late middle to the early late Pleistocene, and agree with other known Teratornithidae taxa in size and morphology. We updated the taxonomy of the family and analyzed its fossil record in the Pleistocene of both Americas. The available evidence suggests that forms related to Teratornis lived in the South American Pampas around the time of the Last Interglacial (MIS 5), but they were restricted to North America during the latest Pleistocene (late MIS 3–early MIS 1). The contrasting latest Pleistocene record of teratorns between North and South America is not easy to understand, especially because the supposed flight capacity of these birds did not prevent them from crossing large geographical barriers. Although a bias in the fossil record cannot be ruled out, it is possible that the teratorns were limited in South America by paleoclimatic–paleoecological factors as yet undetermined, and/or that the northern and southern Pleistocene species had very dissimilar specializations. In relation to the latter, the previous inferences on the teratorn paleobiology without phylogenetic support are preliminarily questioned here.